Application Of Back Massage Therapy To Reduce Pain In Gastritis Patients Through The Application Of Peplau's Theory At Lingkar Timur Community Health Center Bengkulu, 2025 - Lestari, Rapita; Susanti , Meri Epriana (Utami Publisher, 2026)
Gastritis is defined as pain or discomfort in the upper abdomen. Patients with gastritis or stomach ulcers usually present with additional complaints ranging from nausea to vomiting. Other symptoms such as bloating, early satiety, decreased appetite, and frequent belching may also occur.The purpose of this study is to apply back massage therapy to reduce pain in gastritis patients through the application of Peplau's theory within the working area of Lingkar Timur Community Health Center, Bengkulu City, in 2025.The method used in this final nursing case study involved two gastritis patients from the working area of Lingkar Timur Community Health Center, Bengkulu City. Nursing care was provided over three sessions.The results obtained after the intervention showed that back massage therapy effectively reduced pain levels in gastritis patients. Pain scale decreased from 6 before the intervention to 0 after back massage therapy.It can be concluded that there is a significant effect of back massage therapy on reducing pain in patients with gastritis. The researcher recommends that gastritis sufferers within the working area of Lingkar Timur Community Health Center adopt back massage therapy to help reduce and eliminate pain.